THE EFFECT OF ACADEMIC SELF MANAGEMENT AND READING ANXIETY TO STUDENTS’ READING COMPREHENSION IN EFL CLASSROOM - Wilany, Eka; Dewi, Desi Surlitasari (Universitas Riau Kepulauan, 2017)
The objectives of this research were to find out the interaction of academic self management and reading anxiety in English reading comprehension, the difference of students high and low reading anxiety in reading comprehension, the difference of reading comprehension students having higher academic self management have high and low reading anxiety and the difference between low academic self management that have high and low reading anxiety in reading comprehension. Expost facto was employed as the design of the study with Riau Kepulauan University as the population. To measure students reading anxiety and academic self management, it was used questionnaires. Furthermore, reading test was used for measuring the students’ reading comprehension. Data analysis used Two –Way ANAVA, then Tuckey Test. It was found that there was difference between high and low reading anxiety students in which Qcount(3.47) Q table (2.89). Then the interaction showed students academic self management and reading anxiety in reading comprehension, the score of Qcount bigger than Qtable (12,223,07). Next, high academic self management between high and low reading anxiety was found different. It was counted that Qcount (9.00) Qtable (3.01). In contrast, there was no difference of reading comprehension between students low academic self management having and low reading anxiety. It was calculated that Qcount (-0.08)Q table (3.01). Keywords: Academic Self Management, Anxiety, Reading Comprehension